Jogo como recurso didático no ensino da matemática - Schmidt, Rosmari Bortolini (2016)
The appropriation of mathematical knowledge meanings along school life is the subject of numerous discussions among educators, including those that deal with the need of developing proposals which foster student learning and development. In this view, this research, developed within the line of Education and Language Processes, brings as its main theme the games involving problem solving on the specific content of financial mathematics. The issue guiding the study was translated into the following question: to what extent do games contribute to the implementation or expansion of school mathematical knowledge? Its main goal was to investigate how game development can contribute to learning, with regard to education or extension of mathematical concepts. The games were developed with Junior High 8th grade students of a municipal school in Piratuba/SC, and were recorded by filming and photographing. In the foundations of the research process, the main authors related to games (Piaget, Wallon, Lara, Borin) were taken into account as well as the historical-cultural theory (Vygotsky, Palangana, Moura). The analysis was presented in episodes, compounded according to each game being developed, in a microgenetic approach focusing on events promoted through social interactions that were being constituted during the games. It was found that the use of games on problem scenarios, used intentionally and consciously by the teacher in the classroom, promotes moments of social interaction with exchanges of ideas, cooperation, thought organization and preparation of action plans among the participants, which all provide the students both the application and extension of mathematical knowledge.